The structure and psychometric properties of the Screening Scale for Language Development - Spanoudis, George; Kanikli, Antri (Psychology: the Journal of the Hellenic Psychological Society, 2023)
Identifying developmental language difficulties is a widely recognized necessity, as it is the first step to diagnosing and treating language disorders. The Greek language has, however, lacked standardized screening scales for preschool children. Screening Scale of Language Development (SSLD) has been developed based on recent research on clinical markers and prognostic factors of developmental language difficulties at preschool age. SSLD reliability and validity were examined in this study. A bifactor structure provides an adequate explanation for the data and confirms the new scale's validity and reliability. To validate the SSLD and its use in clinical practice, more studies must be conducted.